Tinjauan Hukum Islam terhadap Pembagian Harta Warisan di Desa Lolo Hilir Kecamatan Bukit Kerman Kapubaten Kerinci - Riko Pirman; Robi'atul Adawiyah; Sulhani Sulhani; Rasito Rasito; Tri Endah Karya Lestiyani (NALAR FIQH: Jurnal Hukum Islam, 2022)
This study aims to reveal a review of Islamic law on the distribution of inheritance based on adat in Lolo Hilir Village, Bukit Kerman District, Kerinci Regency. This study uses a qualitative approach with data collection methods through observation, interviews, and documentation. Based on the research conducted, the results and conclusions are obtained that the review of Islamic law on the distribution of inheritance based on adat in Lolo Hilir Village is allowed for reasons that are justified by Islam and sharia, where women's morality is more responsible for their families. Therefore, the distribution of inheritance in Lolo Hilir Village is given the right to use for women, the inheritance can only be used and cannot be sold and property rights. Men cannot use it, but when the inheritance is sold, the man gets a share according to the agreement, but it is possible for the man to use the inheritance according to the agreement. In Islam, inheritance law is obligatory and the distribution has been regulated, but it can change due to certain circumstances and reasons. Over time, many women in Lolo Hilir Village have been able to work, so there are often conflicts over the distribution of this inheritance, but there has been a bright spot, the inheritance is distributed evenly, but if it is implemented something is not possible, then it is resolved by adat to uphold the welfare and justice of the people of Lolo Hilir Village.